2017
DOI: 10.1002/etc.3748
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium, manganese, and lead on locomotor activity and neurexin 2a expression in zebrafish

Abstract: The synaptic adhesion protein Neurexin 2a (Nrxn2a) plays a key role in neuronal development and is associated with cognitive functioning and locomotor behavior. Although low-level metal exposure poses a potential risk to the human nervous system, especially during the developmental stages, little is known about the effects of metal exposures on nrxn2a expression during embryonic development. We therefore exposed wild-type zebrafish embryos/larvae to cadmium (CdCl ), manganese (MnCl ), and lead ([CH COO] Pb), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Marins et al in their fresh study from 2019 found that long-term exposure to Fe and Mn in a concentration commonly found in groundwater may cause damage to chromosome levels and changes in locomotor and exploratory behaviors of adult zebrafish [61]. It was further concluded by Tu H. et al that developmental exposure to Mn along with Cd and Pb statistically reduced the velocity and distance of the larval swim of zebrafish [62]. Altenhofen et al studied the effect of MnCl 2 exposure on cognition and exploratory behavior in adult and larval zebrafish.…”
Section: Discussionmentioning
confidence: 96%
“…Marins et al in their fresh study from 2019 found that long-term exposure to Fe and Mn in a concentration commonly found in groundwater may cause damage to chromosome levels and changes in locomotor and exploratory behaviors of adult zebrafish [61]. It was further concluded by Tu H. et al that developmental exposure to Mn along with Cd and Pb statistically reduced the velocity and distance of the larval swim of zebrafish [62]. Altenhofen et al studied the effect of MnCl 2 exposure on cognition and exploratory behavior in adult and larval zebrafish.…”
Section: Discussionmentioning
confidence: 96%
“…Behavioral response was applied for decades as an indicator of toxicological impact within neurons [ 47 , 48 , 49 ]. Previous studies reported behavioral and locomotor activity alterations influenced by divalent zinc and/or other heavy metals in different species; however, only developmental toxicity of ZnCl 2 in zebrafish embryos was addressed [ 50 , 51 , 52 ]. In contrast, our pioneer study demonstrated, for the first time, that adult zebrafish exposed to ZnCl 2 had reduced locomotor behavior, average speed, entries to the upper zone, and total distance traveled.…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish embryos and larvae, available studies on Pb toxicity mainly focused on neurotoxicity, neurodevelopmental, and neurobehavior effects [40,[43][44][45][46][47][48]. Surprisingly, morpho-functional investigations during the sensitive phase of development are scarce, and only a few studies have furnished an overall morphological evaluation [45,[49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…In zebrafish embryos and larvae, available studies on Pb toxicity mainly focused on neurotoxicity, neurodevelopmental, and neurobehavior effects [40,[43][44][45][46][47][48]. Surprisingly, morpho-functional investigations during the sensitive phase of development are scarce, and only a few studies have furnished an overall morphological evaluation [45,[49][50][51][52][53]. Moreover, all available information on fish deals with high lead concentrations, and there is a lack of research on the adverse effects of lead at environmentally relevant concentrations [53].…”
Section: Introductionmentioning
confidence: 99%